Translating the determinant aspects on the study design in the dental implant field - Pereira, Marta Maria Alves [UNESP]; Dini, Caroline; Souza, João Gabriel Silva; Barão, Valentim Adelino R.; de Avila, Erica Dorigatti [UNESP] (MJS Publishing, Medical Journals Sweden AB, 2023)
Objective: In this article, we analyzed the important categories capable of interfering with the determinants of scientific advancement in the type of study, considering seven leading journals over a 20-year. Methodology: A bibliometric review was performed at the website of well-established implant dentistry journals in five-time points defined to represent a 20-year period of observation. The measures associated with the type of study design were: the country of origin of the article, country income, continent of the corresponding author, inter-institutional collaboration, interdisciplinary collaboration, type of funding, and topic of research. Logistic regression was used in the multiple models to identify the exploratory factors associated with the type of study. Results: From a total of 1,944 articles, 50.6% comprised clinical studies. High-income countries and continents stood out for developing more clinical research than others. Since research funders request more collaborative research, overall clinical studies depended upon more inter-institutional collaboration than the others. Most clinical studies were partly supported by research institutes or universities and by industry. About the research topic, the majority of the clinical and animal studies disclosed surgical procedures. Conclusions: High-income countries and continents are more likely to develop clinical studies in the surgical procedures field. The highest collaborations in terms of the number of institutions and funding sources are more prevalent in clinical research designs. Indeed, most in vivo studies in dental implant fields are performed to evaluate new materials or even new surgical procedures.
Keywords: Bibliometric analysis; clinical study; dental implants; type of study